ANTIOXIDANT POTENTIAL ON CHITOSAN OF MANGROVE CRAB (Scylla serrata) SHELL WITH THE ADDITION OF DIFFERENT NaOH - Sukmiwati, Mery; Karnila, Rahman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRAK This research was aimed to determine the effect of the different concentration of NaOH to the quality of chitosan and antioxidant potential on chitosan of mangrove crab (Scylla serrata) shell. The experimental method was used in this research with Completely Randomized Design (CRD), which consists of three levels of treatment with different NaOH concentrations i.e. KT1 (50%), KT2 (55%) and KT3 (60%). A series of research activities was divided into 3 stages, namely: 1) preparation of the mangrove crab shell flour, 2) extraction of mangrove crab shell chitosan, 3) antioxidant assay on mangrove crab shell chitosan. The result showed that the different concentration of NaOH was significantly affect to the moisture content of chitosan, and was very significantly affect to the ash content of the mangrove crab shell chitosan, with value of deasetilation degree of KT1, KT2, and KT3 was 53.42%, 62.46%, and 68.21%, respectively. Meanwhile the IC50 value of KT1, KT2, and KT3 was 883.7600 µg/mL, 528.1745 µg/mL and 737.9175 µg/mL, respectively. The IC50 values indicated that the antioxidant activity on chitosan of mangrove crab shell was classified as weak or inactive. Keywords: antioxidants, mangrove crab Shell, extracting, Chitosan.